2015
DOI: 10.1002/cbin.10404
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cells suppressing activation of allogeneic cytokine‐induced killer/natural killer cells either by direct or indirect interaction

Abstract: Bone marrow mesenchymal stem cells (MSC) were recently found to be associated with some special immunological characteristics, the immunoregulatory effect of MSC was dose-dependent. Low amount of MSC was associated with mild immunosuppression or even immune activation, while the high amount of that was associated with significant immunosuppressive effect. In this study, by using a transwell system, we explored the effect of MSC on the cell cycle, apoptosis rate and the expression of CD69, an activation marker,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
0
12
2
Order By: Relevance
“…shown to inhibit the proliferation of activated T cells in vitro and in vivo. Besides, compared with NK cells cultured alone, MSCs highly elevated NK cells' apoptosis rate in co-cultures, this finding was different from another scholar,31 and this might be due to the different cytokines and their concentration. In the present study, BMMSCs and DPSCs were observed to inhibit the proliferation of NK cells; this was similar to the most studies.…”
contrasting
confidence: 84%
“…shown to inhibit the proliferation of activated T cells in vitro and in vivo. Besides, compared with NK cells cultured alone, MSCs highly elevated NK cells' apoptosis rate in co-cultures, this finding was different from another scholar,31 and this might be due to the different cytokines and their concentration. In the present study, BMMSCs and DPSCs were observed to inhibit the proliferation of NK cells; this was similar to the most studies.…”
contrasting
confidence: 84%
“…MSCs are frequently used, either as cellular therapy or within implanted material, in the clinical setting for orthopedic injuries, cardiovascular diseases and other pathological conditions, such as cardiac tissue repair following myocardial infarction . MSCs are present in most tissues and contribute to tissue regeneration, thanks to their ability to differentiate toward mesodermal lineages and to modulate the tissue immune microenvironment . hMSCs have been shown to mediate immune‐modulation, not only by increasing the proportion of CD8 + CD28 − T reg ‐cells, but also enhancing their ability to hamper naïve CD4 + T‐cell proliferation and activation, as shown by in vitro coculture of hMSCs with T cells .…”
Section: Interaction Between Immune Cells and Other Cell Populations mentioning
confidence: 99%
“…It should be noted that transplantation of MSCs from other sources have been shown to escalate Treg population as a mechanism of exerting immunosuppression [53,54]. For example, in a 25-yearold severe SLE patient with multiple life-threatening complications and refractory to conventional cyclophosphamide (CYC) therapy, Wang et al [55], reported that transplantation of autologous hematopoietic stem cell and MSCs re-established self-tolerance in SLE by increasing CD4+CD25+FoxP3+Treg cells in PBMCs.…”
Section: Discussionmentioning
confidence: 99%